High incidence of preventable deaths during childhood in Porto Velho, Rondonia - Brazil - Moreira, Kátia F. A.; Costa, Adriano P. da; Escobar, Ana L.; Valenti, Vitor Engrácia [UNESP]; Abreu, Luiz Carlos de; Roque, Adriano L.; Tavares, Carlos M. (My University, 2014)
Background: We aimed to estimate and analyze epidemiological profile of deaths during childhood. Method: We used the databases of deaths provided by Information System of mortality between 2006 and 2010. We selected only those records where the occurrence of deaths corresponded to Porto Velho city and those who were aged between 12 and 48 months old at the moment of death. We examined only deaths from preventable causes and poorly defined. Results: The total number of deaths was estimated to be 103, 48.6% male. High frequencies of deaths occurred (39.8%) in children before reaching two years old. Vast majority of deaths (66.9%) was due to preventable causes, 18.4% by poorly defined causes and nearly one in three by external causes. Approximately one in four were due to traffic accidents, 41.9% by drowning and submersion. Also, there were significant frequencies of deaths associated with respiratory diseases (17.5%) and infectious and parasitic diseases (16.6%). Conclusion: These findings reinforce the importance of studies of infant mortality, drawing attention to the debate on policy design to reduce childhood deaths, especially in acting on preventable causes.